Development of Physical Fitness Measurement on Senior High School Students - Aziz, Ishak (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: This study aims to provide another alternative for physical education teachers in measuring the physical fitness of high school students by measuring the tests of jumping, push-ups, and sit-ups and determining the correlation between the three activities as a condition for determining physical fitness. MATERIALS AND METHODS: The random sampling method used to select respondents, and as a result, as many as fifty-two students chose as respondents. The device included a leaping test, push-ups, sit-ups, and a 2400 m run test. RESULTS: The results showed that the validity coefficient between X1 and Y is r = −0.352. The push-up meets the requirement to measure the endurance of blood circulation and breathing with the acquisition of r = −0.007. Sit-ups measured the endurance of blood circulation and respiration with the acquisition of r = −0.164. The relationship between the combined degree of ability X1, X2, and X3 with a run of 2400 m obtained r = 0.47. The reliability coefficient for X1 was r = 0.82, X2 was r = 0.83, and X3 was r = 0.85. CONCLUSION: It concluded that the jump test, push-ups, and sit-ups together could be used as another alternative to measure high school students’ physical fitness through facilities and infrastructure compared to the 2400 m running test.